2018
DOI: 10.1055/a-0639-5035
|View full text |Cite
|
Sign up to set email alerts
|

Lack of a Dose Response from 7 Days of Ischemic Preconditioning in Moderately trained Cyclists

Abstract: Ischemic preconditioning (IP) has a small benefit on exercise performance, but differences in the IP method, performance tasks and exercise modality have made providing practical coach guidelines difficult. We investigated the performance-enhancing effects of IP on cyclists by comparing the frequency of IP application over a 7-day period. Using a randomized, sham-controlled, single-blinded experiment, 24 competitive age-group track cyclists (38±12 years) were assigned to one of three twice-daily (sham: 20 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 31 publications
3
17
0
Order By: Relevance
“…These observations were made beyond the late phase (72-h) of IPC-mediated protection and, therefore, importantly do not reflect the acute effects of IPC (Yellon and Baxter 1995;Loukogeorgakis et al 2005). Whilst there is limited research examining the repeated nature of IPC on performance, our findings contrast the +13 % increase in ̇O 2max reported in untrained individuals (̇O2max ~ 39 ml•kg -1 •min -1 ) (Lindsay et al 2017), but are further supported by work from the same group where no change in ̇O 2max was observed in moderately fitter individuals (̇O2max ~ 50 ml•kg -1 •min -1 ), both immediately and 7-d following a repeated IPC procedure (Lindsay et al 2018). Caution should be exercised when interpreting the large effects reported, to date, due to potential training effect in the recreational population, which was noted by the authors (Lindsay et al 2017).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…These observations were made beyond the late phase (72-h) of IPC-mediated protection and, therefore, importantly do not reflect the acute effects of IPC (Yellon and Baxter 1995;Loukogeorgakis et al 2005). Whilst there is limited research examining the repeated nature of IPC on performance, our findings contrast the +13 % increase in ̇O 2max reported in untrained individuals (̇O2max ~ 39 ml•kg -1 •min -1 ) (Lindsay et al 2017), but are further supported by work from the same group where no change in ̇O 2max was observed in moderately fitter individuals (̇O2max ~ 50 ml•kg -1 •min -1 ), both immediately and 7-d following a repeated IPC procedure (Lindsay et al 2018). Caution should be exercised when interpreting the large effects reported, to date, due to potential training effect in the recreational population, which was noted by the authors (Lindsay et al 2017).…”
Section: Discussionsupporting
confidence: 50%
“…Repeated application of IPC across a number of days, thereby increasing the stimulus, has demonstrated clinical efficacy in a dose-dependent manner (Yamaguchi et al 2015). While a small number of studies have examined the repeated application of IPC on exercise performance (Foster et al 2014;Lindsay et al 2017Lindsay et al , 2018, there has been no investigation of the associated physiological adaptations that might support an ergogenic effect. For example, notable improvements in systolic and diastolic blood pressure (Jones et al 2014), vascular health (Jones et al 2014) and skeletal muscle oxidative function (Jeffries et al 2018), if translated to the exercising muscle, could enhance the efficiency of ATP turnover and increase blood flow, leading to improved tissue oxygenation and metabolite removal.…”
Section: Introductionmentioning
confidence: 99%
“…In athletes, application of IPC alone would likely be insufficient to induce such improvements (Marocolo et al, 2018 ). Indeed, IPC applied once or twice a day for 7 consecutive days failed to improve 4-km TT in trained cyclists (Lindsay et al, 2018 ), but combining IPC with high-intensity training could trigger larger adaptations. Surprisingly, trained middle-distance runners did not improve VO 2 max or 1-km TT performance after 8 weeks of training alone or when preceded by IPC (Slysz and Burr, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…increase in peak power output, mean power output, and fatigue index) during repeated Wingate tests (Lindsay et al, 2017 ) have also been reported. However, in athletes, the application of IPC alone would likely be insufficient to induce such improvements and, in fact, IPC applied once or twice a day for 7 consecutive days failed to improve 4-km TT performance in endurance cyclists (Lindsay et al, 2018 ). To date, only one study used IPC prior to high-intensity training sessions, but authors reported that neither training alone nor training preceded by IPC improved VO 2 max and 1-km TT running performance in distance runners after 8 weeks (Slysz and Burr, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the four-cycle protocol demonstrated an improvement in resistance performance compared to the eight-cycle protocol. The second study (24) , on the other hand, veri ed whether IPC applied different numbers of times per day improves performance, however, daily frequency was not a determining factor for improving performance (23,24) . Another factor that can determine the results of IPC is the pressure of occlusion generated in the period of ischemia, however, no studies were found that analyzed these effects in the recovery period after an EIMD.…”
Section: Introductionmentioning
confidence: 99%